Modern Techniques to Study Biokinetics of Nanoobjects in Living Organisms - Antsiferova , A. A.; Kashkarov, P. K. (Research Highlights in Science and Technology Vol. 1, 2023)
Strictly, Nanosafety is a field of Biomedicine. However, the majority of the techniques developed and applied for research in Nanosafety is interdisciplinary. Investigation of biokinetics of nanoobjects is an important branch of Nanosafety, which allows to estimate the toxicological load in the tissues of an exposed organism and predict therapeutic effect of the medicine. The present chapter reviews various modern techniques to study the biokinetics of nanoobjects in living organisms. Common patterns of the biokinetics of exogenous substance in a living organism and the major principles of a toxicological experiment are presented. A capacious and comprehensive presentation of Atomic Emission Spectrometry; Mass Spectrometry; X-ray Fluorescence Spectroscopy and Nuclear Physical Techniques such as Neutron Activation Analysis, Radiotracer Technique, In situ Neutron Activation Analysis; Microscopy and the specifics of their application in this area of research are given. General methodological recommendations for the experiment planning are formulated. The theoretical approach to study nanoobject biokinetics based on the PBPK-modelling is considered. Examples of original studies on the biokinetics of TiO2 and Ag nanoparticles implemented with the use of the considered techniques are presented. Authors attempted to share their own experience of research in the field of Nanosafety.